Development of the risk management system of the enterprises - aviation equipment lifecycle participants - I. I. Zvyagintseva; T. I. Zueva (Управление)
The knowledge-intensive enterprises, in the course of their activity, face a combination of various threats and the attendant risks. In the article the authors proved the importance of the problem of improving the risk management system in the aviation industry. The relevance of this study is justified by the need to improve the quality of management decisions taking into account the impact of risks in the implementation of complex innovative projects for the creation and operation of aviation equipment. The article contains the results of a study to identify new approaches to solving the problem of effective management of aviation industry enterprises, including risk management, as part of the overall management system of the enterprise. The existing risk management system, substantiates the main shortcomings and develops proposals for its improvement are described. As a result of the work done the authors developed a risk management system that allows timely detection of risk factors and assess the impact of the implementation of a risk event on key performance indicators of enterprises. The application of the proposed risk management system will allow to provide a new approach to risk-oriented management in the industry, with the possibility of making effective management decisions at different levels of management, from sectoral to project management, which will increase the level of economic security of enterprises in modern conditions, ensure effective interaction between enterprises with the ability to make managerial decisions at different levels of management - from project to industry. The economic effectiveness of the proposed risk management system will be manifested in the selection of the optimal management solution, with efficient use of limited resources, in improving the indicators that characterize the economic security of enterprises.